Discovery of novel PDE9 inhibitors capable of inhibiting Aβ aggregation as potential candidates for the treatment of Alzheimer’s disease - Su, Tao (Sci Rep, 2016)
Recently, phosphodiesterase-9 (PDE9) inhibitors and biometal-chelators have received much attention as potential therapeutics for the treatment of Alzheimer’s disease (AD). Here, we designed, synthesized, and evaluated a novel series of PDE9 inhibitors with the ability to chelate metal ions. The bioassay results showed that most of these molecules strongly inhibited PDE9 activity. Compound 16 showed an IC(50) of 34 nM against PDE9 and more than 55-fold selectivity against other PDEs. In addition, this compound displayed remarkable metal-chelating capacity and a considerable ability to halt copper redox cycling. Notably, in comparison to the reference compound clioquinol, it inhibited metal-induced Aβ(1-42) aggregation more effectively and promoted greater disassembly of the highly structured Aβ fibrils generated through Cu(2+)-induced Aβ aggregation. These activities of 16, together with its favorable blood-brain barrier permeability, suggest that 16 may be a promising compound for treatment of AD.